Pengembangan Media Pembelajaran Roda Berputar untuk Materi Trigonometri - Clara Angelina; Julinda Siregar; Siti Alfiyyah Atikah Kusnadi; Miftahul Jannah; Syifa Ismi Wardani; Leonard Leonard (EduResearch Mitra Inovasi, 2021)
The purpose of this research is to develop a game-based learning media, which is the Matemetri Wheel for High Schools. The research method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the study showed that the Wheel of Mathematics is an innovative and interesting learning media. With this Roda Matemetri media, it can foster student interest and interest in learning trigonometry. The Matemetri Wheel can also help the learning process, as the teacher can more easily convey trigonometric material so that students can easily understand it. In addition, the Matemetri Wheel can enliven the classroom atmosphere and make active learning. Thus, it can be concluded that the learning media Roda Matemetri for trigonometry material is feasible to use.